Beyond the Simple Association Between Romantic Attachment Insecurity and Dyadic Coping: An Examination of Romantic Perfectionism as a Mediator. (2019) - Lafontaine, Marie-France; Péloquin, Katherine; Levesque, Christine; Azzi, Stéphanie; Daigle, Marie-Pierre; Brassard, Audrey
Abstract: This study examined the mediating role of romantic perfectionism in the associations linking romantic attachment insecurity and self-perceived dyadic coping in a community sample of 170 mixed-sex couples. Path analyses, based on the actor-partner interdependence model, revealed that other-oriented perfectionism in men and women mediated the link between their own attachment-related avoidance and dyadic coping. Other-oriented perfectionism in women mediated the link between their own attachment-related anxiety and dyadic coping. Findings contribute to advancing knowledge about the intrapersonal and interpersonal mechanisms underlying coping processes in couples. Results also inform clinical interventions targeting attachment insecurities and perfectionism in the context of romantic relationships.